2015
DOI: 10.3109/15563650.2015.1054501
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of abdominal computed tomography with and without oral contrast in diagnosis of body packers and body stuffers

Abstract: There is a remarkable gap between detection of existence and number of packets/baggies reported by the radiologists and the real condition of the patients. A close teamwork between radiologists and toxicologists is needed to manage these problematic cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 21 publications
0
15
0
2
Order By: Relevance
“…Because of this we can use another more sensitive imaging modality. CT is clearly the best method for detecting foreign bodies and the use of helical CT has been widely advocated in the literature for detection, location and density characterization of various non-metallic foreign bodies (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Ultrasound (USG) has also been used for detection, but it has limited resolution, and will miss a significant number of packets (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this we can use another more sensitive imaging modality. CT is clearly the best method for detecting foreign bodies and the use of helical CT has been widely advocated in the literature for detection, location and density characterization of various non-metallic foreign bodies (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Ultrasound (USG) has also been used for detection, but it has limited resolution, and will miss a significant number of packets (18).…”
Section: Discussionmentioning
confidence: 99%
“…After the absence of drug intoxication symptoms, we decided to perform a non-contrast abdominal CT scan. CT findings showed the presence of more than thirty rounded foreign bodies striking from stomach to rectum (figure [1][2][3][4]. At the fallowing the patient admitted that he has swallowed packages of cocaine.…”
Section: Case Reportmentioning
confidence: 99%
“…31 Shahnazi and colleagues evaluated body packers and stuffers but did not advocate endoscopic retrieval due to fear of rupture. 32 In general, most experts try to avoid endoscopy due to the fear of baggie rupture although recent studies have suggested this technique as a potential treatment in body stuffers if the condition is optimum and the GI specialist performing the endoscopy is highly skilled. 4 Invasive surgical approaches are only recommended when the process of passage is delayed or complicated by rupture and endoscopy has not located the baggies.…”
Section: Discussionmentioning
confidence: 99%
“…Eng et al (31) reported a false negative finding of non-contrast CT in a verified case of cocaine body stuffing. A study on 24 body stuffers showed that although noncontrast CT was not as sensitive as that in body packers, it was still a better choice in detecting small bags compared to contrast CT (50). Another study by the same authors (51, 52) advocates low-dose CT as a screening method for body stuffers if the packages are bigger than one centimetre in size.…”
Section: Imagingmentioning
confidence: 99%